2018
DOI: 10.1098/rsos.171541
|View full text |Cite
|
Sign up to set email alerts
|

Selective and metal-free epoxidation of terminal alkenes by heterogeneous polydioxirane in mild conditions

Abstract: Polydioxirane (PDOX) was prepared by the treatment of polysalicylaldehyde with Oxone and was found as a selective, highly efficient and heterogeneous reagent for epoxidation of alkenes which can be successfully isolated. This work also introduced a simpler, safer and milder way for epoxidation of alkenes with dioxirane groups than before. PDOX can be simply recovered from the reaction mixture by plain filtration and reused for eight runs without significant reactivity loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Stability, durability and, consequently, recyclability of a heterogeneous catalyst are prominent and important factors from economical, energy saving, and environmental points of view; [39][40][41] the rigid inorganic structure of the sulfated zirconium oxide solid support along with the magnetic properties of the CuFe 2 O 4 moieties made the catalyst recoverable and reusable and minimized any metal leaching. The recyclability of the catalyst was investigated in the Sonogashira cross-coupling reaction of phenylacetylene and iodobenzene in the presence of NaOH at 60 C. The catalyst was recovered in each cycle, washed with EtOH (2 Â 5 mL) and reused in the next run without any purication or pre-activation.…”
Section: Recoverability Studiesmentioning
confidence: 99%
“…Stability, durability and, consequently, recyclability of a heterogeneous catalyst are prominent and important factors from economical, energy saving, and environmental points of view; [39][40][41] the rigid inorganic structure of the sulfated zirconium oxide solid support along with the magnetic properties of the CuFe 2 O 4 moieties made the catalyst recoverable and reusable and minimized any metal leaching. The recyclability of the catalyst was investigated in the Sonogashira cross-coupling reaction of phenylacetylene and iodobenzene in the presence of NaOH at 60 C. The catalyst was recovered in each cycle, washed with EtOH (2 Â 5 mL) and reused in the next run without any purication or pre-activation.…”
Section: Recoverability Studiesmentioning
confidence: 99%
“…(39) Kinetic studies showed that in substituted cinnamonitriles the p- Polydioxirane 36 was shown to be a new and powerful epoxidizing reagent for both alkyland aryl-substituted alkenes. (40) In addition, the CH 2 OH group was tolerated by this reagent.…”
Section: 32 Epoxidation Reactionsmentioning
confidence: 98%
“…223 PDOX 275, a shelfstable compound, was generated in situ from polysalicylaldehyde (PSA, 274, 0.5 g) and Oxone® (Scheme 60). The synthesis of PDOX began from salicylaldehyde (272), first formylation to 273 followed by polycondensation with 274, and finally, oxidation with Oxone® (10 mmol) in the presence of NaHCO 3 (10 mmol) led to polymer 275, the latter exhibited substantial improvements compared to 9 in terms of stability, recyclability, and reactivity in aqueous media 223 For example, 275 was stable at room temperature for up to 1 week, and could be recycled up to 8 times without any loss of reactivity, and removable by simple filtration. The generation of 275 from 274 was observed by 1 H NMR analysis, and it was further supported by UVvisible and thermogravimetric (TGA) analysis.…”
Section: Epoxidation Of Alkenes/arenesmentioning
confidence: 99%